1990
DOI: 10.1192/bjp.156.5.689
|View full text |Cite
|
Sign up to set email alerts
|

The Friendships and Recent Life Events of Anxious and Depressed School-Age Children

Abstract: The number of moderate to severe undesirable life events and the quality of friendships were compared between a consecutive series of 100 children aged 7-16 years with emotional disorders and a series of community controls matched for age, sex, and social class. Undesirable events and friendship difficulties exerted independent direct effects of similar magnitude on the probability of developing emotional disorders; 33% of disturbed children experienced both adversities compared with 6% of controls. An additiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
85
0
2

Year Published

1995
1995
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(99 citation statements)
references
References 17 publications
12
85
0
2
Order By: Relevance
“…This is surprising given that as most anxiety disorders take a chronic course, environmental factors important to onset are likely to be those present in childhood (Rapee and Bryant 2008). The limited evidence available indicates that anxious children experience a greater number of life events and some specific chronic adversities in the 12-month period preceding the onset of anxiety in comparison to healthy controls (e.g., Goodyer et al 1988Goodyer et al , 1990.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…This is surprising given that as most anxiety disorders take a chronic course, environmental factors important to onset are likely to be those present in childhood (Rapee and Bryant 2008). The limited evidence available indicates that anxious children experience a greater number of life events and some specific chronic adversities in the 12-month period preceding the onset of anxiety in comparison to healthy controls (e.g., Goodyer et al 1988Goodyer et al , 1990.…”
mentioning
confidence: 99%
“…First, in two of the studies anxious children were identified by an unstructured psychiatric interview and were obtained from severely disturbed populations attending in-patient and outpatient hospital-based psychiatric clinics (Goodyer et al 1988(Goodyer et al , 1990, which is not characteristic of most anxious children. The only study to identify children using a structured psychiatric interview (Gothelf et al 2004) relied on a child self-report checklist to assess life events and thus failed to provide a more independent determination of the "severity" or impact of stressors.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Moguće je da stres koji može nastati kao posljedica sudjelovanja u vršnjačkom zlostavljanju zapravo dovodi do povećanog rizika za razvoj psiholoških poteškoća. Da stresni životni događaji imaju važan utjecaj u nastanku psiholoških poteškoća kod djece, potvrđeno je već u ranim istraži-vanjima koja su se bavila ispitivanjem utjecaja stresa na mentalno zdravlje djece (Brown i Harris, 1978;Goodyer, Wright i Altham, 1990;Boivin, Hymel i Bukowski, 1995;Sandberg, Rutter, Pickles, McGuinness i Angold, 2001;Arsenealut, Walsh i Kali Trzesniewski, 2006). U periodu rane adolescencije djeca su posebno podložna sudjelovanju u vršnjačkom zlostavljanju i ono je u toj dobi posebno intenzivno i perzistentno, što znači učestalost stresnih situacija, a samim tim i povećan rizik za razvoj psiholoških poteškoća (Rigby, 1999).…”
Section: Tablicaunclassified
“…While the mechanism linking early adversity and multiple lifetime exit events to juvenile depression is unclear, evidence suggests that low self-esteem and ongoing friendship difficulties may be vulnerability factors (39,40). In the range offactors that intensify or ameliorate response to a risk factor, vulnerability and protective factors have been seen as opposite poles (41).…”
Section: Life Eventsmentioning
confidence: 99%